2022
DOI: 10.3389/fonc.2022.889624
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of MicroRNA-371a-3p (M371) Can Predict Absence or Presence of Vital Disease in Residual Masses After Chemotherapy of Metastatic Seminoma

Abstract: BackgroundRadiological evaluation of postchemotherapy residual masses of metastatic seminoma is characterized by poor diagnostic accuracy. Serum levels of microRNA-371a-3p (M371) involve high specificity and sensitivity for the primary diagnosis of seminoma. We evaluated if M371 levels can indicate the presence of vital disease in postchemotherapy residual masses in patients with metastatic seminoma.MethodsTwenty-three seminoma patients (median age 52 years) with residual masses had posttreatment measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In the present study, the value of RQ = 5 was considered as ULN by default. As shown in a recent study on residual masses subsequent to chemotherapy in seminoma, some patients without active disease had values slightly above the RQ = 5 threshold (Dieckmann et al 2022b ). Thus, it is currently unclear, if the ULN of 5 of the M371 test is uniformly appropriate.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, the value of RQ = 5 was considered as ULN by default. As shown in a recent study on residual masses subsequent to chemotherapy in seminoma, some patients without active disease had values slightly above the RQ = 5 threshold (Dieckmann et al 2022b ). Thus, it is currently unclear, if the ULN of 5 of the M371 test is uniformly appropriate.…”
Section: Discussionmentioning
confidence: 88%
“…In the PC setting, miR‐371a‐3p also appears to have promising performance characteristics 12 . Recent reports have also indicated miR‐371a‐3p to predict viable disease in cases of PC metastic seminoma 13 …”
Section: Discussionmentioning
confidence: 96%
“…110 miR-371a-3p may also be useful in the assessment of post-chemotherapy residual masses of metastatic seminomas. 90 Using 52 serum samples from 10 patients, miR-371a-3p levels showed to be 13.65-fold higher in patients with proven disease recurrence, when compared with patients without evidence of disease. 89…”
Section: Can Mirnas Be Predictive Of Treatment Response and Disease R...mentioning
confidence: 94%
“…Also, a study with 109 TGCT patients showed that higher levels of these miRNAs at the start of chemotherapy were related to worse clinical outcome and could be useful in early diagnosis of relapses 110 . miR‐371a‐3p may also be useful in the assessment of post‐chemotherapy residual masses of metastatic seminomas 90 . Using 52 serum samples from 10 patients, miR‐371a‐3p levels showed to be 13.65‐fold higher in patients with proven disease recurrence, when compared with patients without evidence of disease 89 …”
Section: Testicular Cancermentioning
confidence: 99%
See 1 more Smart Citation